Pengembangan Alat Peraga Denah Berpetak pada Pembelajaran Matematika Materi Translasi Kelas IX Sekolah Menengah Pertama - Aat Nurhayati (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
The development of this teaching aid is based on the fact that students have low learning motivation in the translation material. The material is not related to real life. Students can only memorize and imitate what is exemplified by the teacher so that their independence is not honed well. The use of teaching aid Denah Berpetak to assist students in building concepts and finding solutions to problems related to translation. The development of this teaching aid goes through several stages including: defining, designing, developing, and disseminating. To get the data from the test results, validity sheets, effectiveness sheets, and practicality sheets were used. The results of the data analysis of the test results showed that Denah Berpetak had valid, very practical, and very effective categories. Therefore, the Denah Berpetak teaching aid can be an alternative teaching aid in the Mathematics learning material for translation.